2016
DOI: 10.1097/rct.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Lesion Histogram Analysis of Apparent Diffusion Coefficient for the Assessment of Cervical Cancer

Abstract: Whole-lesion histogram analysis of ADC maps is useful in the assessment of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…8 The higher correlation coefficients that were obtained in previous studies may be from selection of the region containing the most aggressive tumor region. 8 The mode, the ADC value that appears most frequently in the ADC histogram, was confirmed as significant in distinguishing cervical cancer from normal tissue by Guan et al as well as in predicting a complete response in locally advanced rectal cancer by Cho et al 18,26 However, there was no significant difference between the various histological grades of gastric cancers. Therefore, the mode likely has few potential applications in assessing histological differentiation in gastric cancers.…”
Section: Discussionmentioning
confidence: 92%
“…8 The higher correlation coefficients that were obtained in previous studies may be from selection of the region containing the most aggressive tumor region. 8 The mode, the ADC value that appears most frequently in the ADC histogram, was confirmed as significant in distinguishing cervical cancer from normal tissue by Guan et al as well as in predicting a complete response in locally advanced rectal cancer by Cho et al 18,26 However, there was no significant difference between the various histological grades of gastric cancers. Therefore, the mode likely has few potential applications in assessing histological differentiation in gastric cancers.…”
Section: Discussionmentioning
confidence: 92%
“…[26] Various studies have found that kurtosis of ADC histograms has implications in evaluating cell differentiation and heterogeneity of measured lesions. [2731] With respect to cell heterogeneity, Guan et al [27] found that the normal cervix displays significantly lower ADC kurtosis than cervical cancer because of the homogeneity of normal tissues. Shindo et.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, a positive skewness means a histogram curve with a big left shoulder, suggesting a large portion of highly cellular component, while a negative skewness means a histogram curve with a big right shoulder, suggesting a substantial portion of cystic or edematous tissue [ 17 ]. Guan and Lin et al have demonstrated that cervical cancer had a positive skewness while the skewness of normal cervix was much lower and close to 0 [ 5 , 7 ]. Effective treatment results in a gradual disappearance of tumor’s high cellularity and a more homogeneous distribution of ADC values within the tumor, which makes skewness decrease as we have observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Higher kurtosis indicates a sharper peak and wider tails of the distribution of ADC values. Guan et al have demonstrated that kurtosis of normal cervix was significantly lower than that of cervical cancer because normal tissues were relatively more homogeneous [ 5 ]. After receiving effective therapy, ADC values of the tumor tended to be evenly distributed across the range like normal tissues, which made kurtosis go down following therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation